Acidentes de trabalho grave na construção civil de Uberlândia no ano de 2016: repercussões na vida do trabalhador - Guimarães, Giselle Oliveira de Moraes (2018)
Even today, workers 'sickness and work-related accidents are often treated in an invisible and banal manner, even though it is the greatest harm to workers' health. The priority is the numbers and statistics and not the life of the worker, a reality that hides the real consequences and repercussions of the accident on the life and health of the worker. The objective of this study is to identify and understand the repercussions of the serious work accident in the life of the civil construction worker of Uberlândia/MG, in the year 2016. Through a semi-structured script, interviews with injured workers will be carried out based on the Investigation sheets of the SINAN - System for the Investigation of Notifications of Injuries, sent to CEREST - Reference Center and Worker's Health, in 2016. It was concluded with this research that the serious work accident abruptly interrupts all the life plans of the worker, causing great traumas and great consequences. However, the accident is still not treated with the necessary care in the scope of care in the SUS network, especially with regard to the clinical and psychological follow-up of the injured worker.